2000
DOI: 10.1074/jbc.275.14.10077
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Secretory Phospholipase A2 Causes Rapid Catabolism and Altered Tissue Uptake of High Density Lipoprotein Cholesteryl Ester and Apolipoprotein A-I

Abstract: Plasma levels of high density lipoprotein (HDL) cholesterol and its major protein component apolipoprotein (apo) A-I are significantly reduced in both acute and chronic inflammatory conditions, but the basis for this phenomenon is not well understood. We hypothesized that secretory phospholipase A 2 (sPLA 2 ), an acute phase protein that has been found in association with HDL, promotes HDL catabolism. A series of HDL metabolic studies were performed in transgenic mice that specifically overexpress human sPLA 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
135
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 66 publications
10
135
0
4
Order By: Relevance
“…Decrease in HDL-cholesterol may be related to high concentrations of phospholipase A 2 (ref. 55 ), or to downregulation of the ATP-binding cassette transporter-1 gene 56 . Increased TNF production in patients with septic shock has been shown to correlate with low total cholesterol concentration and concentrations of apolipoproteins A 1 and B (ref.…”
Section: Mechanisms Of Cholesterol Defi Ciencymentioning
confidence: 99%
“…Decrease in HDL-cholesterol may be related to high concentrations of phospholipase A 2 (ref. 55 ), or to downregulation of the ATP-binding cassette transporter-1 gene 56 . Increased TNF production in patients with septic shock has been shown to correlate with low total cholesterol concentration and concentrations of apolipoproteins A 1 and B (ref.…”
Section: Mechanisms Of Cholesterol Defi Ciencymentioning
confidence: 99%
“…It has been suggested that remodeling of HDL through activation of secretory phospholipase A 2 may be an alternative explanation for reduced HDL-c levels during the acute-phase response. Overexpression of this enzyme in mice leads to decreased HDL-c levels and enhanced HDL-c catabolism (29,(38)(39)(40). In addition, inflammation may convert HDL de novo into a more proatherogenic form by coordinate but inverse transcriptional regulation of SAA and Apo A-I in the liver (30).…”
mentioning
confidence: 99%
“…Plasma decay curves for both tracers were generated by dividing the plasma radioactivity at each time point by the radioactivity at the initial 5-min time point after tracer injection. Fractional catabolic rates (FCRs) were determined from the area under the plasma disappearance curves fitted to a bicompartmental model by use of the SAAM II program (22). The use of 3 H-cholesteryl ether affects neither turnover rates in vivo nor SR-BI-mediated uptake of the label into LdlA[mSR-BI] cells in vitro compared with 3 H cholesteryl ester-labeled HDL (data not shown).…”
mentioning
confidence: 99%
“…Plasma total cholesterol, triglycerides, and phospholipids were measured enzymatically using commercially available reagents (Wako Pure Chemical Industries, Neuss, Germany). Pooled plasma samples were subjected to fast protein liquid chromatography gel filtration using a Superose 6 column (GE Healthcare) as described (22). Individual fractions were assayed for cholesterol concentrations as described above.…”
mentioning
confidence: 99%
See 1 more Smart Citation